2014
DOI: 10.3889/oamjms.2015.003
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors and Survival in Non-Small Cell Lung Cancer Patients Treated with Chemoradiotherapy

Abstract: BACKGROUND:According to the literature, performance status, stage-tumor dimension and nodal status, weight loss, were the most important prognostic factors for survival in patients with locally advanced non-small cell lung cancer.AIM:To evaluate the treatment results and the prognostic variables in our patients treated with sequential and concurrent chemoradiotherapy.MATERIAL AND METHODS:In the study 85 patients were randomly assigned to one of the two treatment arms. In the sequential arm, 45 patients had pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 13 publications
0
11
0
1
Order By: Relevance
“…These studies yielded a total of 26 unique CT-related prognostic factors. Most studies had a retrospective cohort study design; nine studies reported a prospective cohort study design [14,20,[31][32][33][34][35][36][37]. In studies reporting follow-up duration, median follow-up ranged from 10 to 70.8 months.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies yielded a total of 26 unique CT-related prognostic factors. Most studies had a retrospective cohort study design; nine studies reported a prospective cohort study design [14,20,[31][32][33][34][35][36][37]. In studies reporting follow-up duration, median follow-up ranged from 10 to 70.8 months.…”
Section: Resultsmentioning
confidence: 99%
“…Thirty inclusions explicitly stated using a clinical staging method [12,14,16,21,31,33,36,, while a combination of clinical and pathological staging was used in 3 studies [61][62][63]. The remaining 32 studies did not specify the staging method [11,13,15,17,18,20,32,34,35,37,. More recent staging systems TNM6 (2002, n = 9), TNM7 (2009, n = 23), and TNM8 (2017, n = 3) were used in 35 publications [11-13,15,16,33, 35,36,38,39,42,46,47,49,51,52,54-57,59,61-63,65,66,68,72,73,75,7 6,78,80,81,85].…”
Section: Resultsmentioning
confidence: 99%
“…Age, gender, performance status, weight loss in the period of 3 months before diagnosis, baseline hemoglobin value, normal leukocytosis and normal neutrophil count, lactate dehydrogenase (LDH) level, hypercalcemia, hypoalbuminemia, tumor dimension, and involved lymph node burden are some of the known prognostic factors in NSCLC. 10,11 Prognostic classifications have been attempted based on gene signatures in resected specimen such as the 15-gene signatures, independent from stage with an overall HR of 15.02 (95% CI: 5.12-44.04) with consistent results in stages I and II. 12 However, till date, a correlation between the above mentioned and many other possibly unknown factors has not been established with varied survival outcomes for patients within a given stage.…”
Section: Discussionmentioning
confidence: 99%
“…Prognostic factors are meant to determine the features of patients and the stage of the cancer before the treatment is started. Some traditional prognostic factors for survival in patients with LUAD and LUSC are performance status, stage-tumor dimension, nodal status, and weight loss [ 35 ]. Moreover, symptoms are seen in advanced stages (stage III or stage IV) in about 70% of patients diagnosed with LC [ 36 ].…”
Section: Introductionmentioning
confidence: 99%